A guide to diagnosis and treatment of Leigh syndrome. Issue 3 (14th June 2013) - Baertling, Fabian; Rodenburg, Richard J; Schaper, Jörg; Smeitink, Jan A; Koopman, Werner J H; Mayatepek, Ertan; Morava, Eva; Distelmaier, Felix
Abstract : Leigh syndrome is a devastating neurodegenerative disease, typically manifesting in infancy or early childhood. However, also late-onset cases have been reported. Since its first description by Denis Archibald Leigh in 1951, it has evolved from a postmortem diagnosis, strictly defined by histopathological observations, to a clinical entity with indicative laboratory and radiological findings. Hallmarks of the disease are symmetrical lesions in the basal ganglia or brain stem on MRI, and a clinical course with rapid deterioration of cognitive and motor functions. Examinations of fresh muscle tissue or cultured fibroblasts are important tools to establish a biochemical and genetic diagnosis. Numerous causative mutations in mitochondrial and nuclear genes, encoding components of the oxidative phosphorylation system have been described in the past years. Moreover, dysfunctions in pyruvate dehydrogenase complex or coenzyme Q10 metabolism may be associated with Leigh syndrome. To date, there is no cure for affected patients, and treatment options are mostly unsatisfactory. Here, we review the most important clinical aspects of Leigh syndrome, and discuss diagnostic steps as well as treatment options.